2020
DOI: 10.1097/sla.0000000000004327
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Hospital Volume on Failure to Rescue after Liver Resection for Hepatocellular Carcinoma

Abstract: Objective: The aim of this study was to evaluate correlation between centers' volume and incidence of failure to rescue (FTR) following liver resection for hepatocellular carcinoma (HCC). Summary Background Data: FTR, defined as the probability of postoperative death among patients with major complication, has been proposed to assess quality of care during hospitalization. Perioperative management is challenging in cirrhotic patients and the ability to recognize and treat a complication may be fundamental to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 42 publications
(42 reference statements)
5
14
0
1
Order By: Relevance
“…In the Italian study on FTR after HCC resection only low centre volume was associated with FTR. 25 The current study confirms that patient factors such as higher age, ASA classification 3, histopathological cirrhosis and disease demographics such as liver resection for biliary cancer and major liver resection are risk factors for occurrence of FTR.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In the Italian study on FTR after HCC resection only low centre volume was associated with FTR. 25 The current study confirms that patient factors such as higher age, ASA classification 3, histopathological cirrhosis and disease demographics such as liver resection for biliary cancer and major liver resection are risk factors for occurrence of FTR.…”
Section: Discussionsupporting
confidence: 80%
“…24 A recent study from Italy focussing on FTR within 90 days after resection of HCC observed an overall FTR rate of 19.2% which ranged between 28.6% in low volume centres and 5.1% in high volume centres. 25 In a German study using invoice data including 18,849 patients from 2009 to 2015 the in-hospital FTR rate was 28.9%. 26 Overall FTR rates of 19.1% in the Netherlands are therefore concordant with the literature.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 8474 patients' data who underwent liver resections for hepatocellular carcinoma were pooled from 15 studies included 15–29 . 301 patients died within 90 days postoperatively.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 8474 patients' data who underwent liver resections for hepatocellular carcinoma were pooled from 15 studies included. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] 301 patients died within 90 days postoperatively. Weighted 90 days mortality was 4.2% with a 95% confidence interval between 3.0% to 5.4% (Figure 3 Forest plot).…”
Section: Weighted 90 Days Mortalitymentioning
confidence: 99%
“…Unfortunately, the studies' reasons for this enormous variance cannot be explained and reflect a general problem in experimental surgery: The robustness and reproducibility of results when applying the same experimental method. In fact, complication management, failure to rescue, is well described in human medicine, but is often not mentioned in any laboratory experiments [33]. One of the reasons for survival difference could be the learning curve, which shows a sharp rise, especially at the beginning of learning.…”
Section: Discussionmentioning
confidence: 99%